Menentukan Strategi Pemasaran Dengan Menggunakan Metode Analisis Swot Pada Kedai Kopi Lgsm Tiban Batam - Sumarya, Edi; Nuraeni, Brigida Endah; Atmojo, Agus Sekti Susila (Tractare: Jurnal Ekonomi-Manajemen, 2022)
The development of the SME (small and medium enterprise) business, especially the coffee shop business sector in the city of Batam has many competitors. With so many competitors, entrepreneurs must determine and have a marketing strategy to increase the value of a product that is sold, promoted to win the competition. The SWOT analysis method (Strength, Weakness, Opportunity, Threat) is a systematic identification of various factors to formulate corporate strategy. This analysis is based on logic that can maximize strengths and opportunities, but simultaneously can minimize weaknesses and threats. The purpose of this research is to find out internal factors which include strengths and weaknesses as well as external factors that must be faced in the form of opportunities and threats, so as to be able to determine the best strategy to be implemented at the LGSM Tiban Batam coffee shop. In this study, the LGSM coffee shop, using the SWOT analysis method which describes the strengths, weaknesses, opportunities and threats, each factor shows the position of the LGSM coffee shop has its advantages, namely the availability of complete facilities. The downside is the availability of parking spaces. Opportunities include food and beverage promotions. Then the threat is that there is another coffee shop that is quite close to the LGSM coffee shop